(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The Objective of this study was to effect of yogic exercises on stress and aggression among the adolescents. An attempt has been made to the total number of subjects (N=50) fifty male students of U.G. level of various colleges of DAVV, Indore, Madhya Pradesh. were practiced different types of yogic exercises like Surya Namaskar, Asanas, Pranayam and Meditation for eight weeks by maintaining a schedule. To determine thes tress, stress questionnaire designed by the International Stress Management Association. Aggression was measured by Buss Perry Aggression Questionnaire. Statistical Analysis descriptive statistics (Mean and standard deviation) Pre-test and Post-test mean were taken and compared by employing ‘t’ test were applied level of significant set at 0.05 level.